Giving voice to headteachers using interpretative phenomenological analysis-IPA: Learning from a Caribbean experience. (January 2018) - Moriah, Mishel P
Successful school leadership is an issue debated globally, but these discussions do not seem to occur within the context of inclusive education in the Caribbean. Although there have been reports indicating steady progression in educational leadership and inclusive practices within the last decade, no planned, long-term innovations have emerged. This article reports part of a small-scale, qualitative study, conducted with 16 headteachers of secondary schools from across Guyana and Trinidad & Tobago. An interpretative phenomenological approachwas used to explore how headteachers ascribe meaning to their unique, lived experiences and how this affects their role in facilitating inclusive education. The study identified a relationship between the lived experiences of headteachers, and their resulting approach to leading their respective schools. There is also potential for the strengthening of educational leadership and inclusion through reflexive practice that promotes equity in the schools' contexts.